Analisis SWOT Pembinaan Squash di Provinsi Riau - Zani, Yulia; Damrah, Damrah; Donie, Donie; Welis, Wilda; Ockta, Yovhandra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research revealed several obstacles in coaching Squash sports in Riau Province. It was found that inadequate facilities and infrastructure, lack of experienced coaches, lack of socialization about Squash , low interest of athletes to train, and limited funds were the main obstacles. The study aims to analyze the Squash coaching process, identify the challenges faced, and find solutions for further development. Qualitative research methods are used using SWOT analysis. The study population involved 15 male athletes and 11 female athletes, while a sample of 10 people was randomly selected, consisting of Riau Province Squash administrators, coaches, and athletes. The results showed the importance of improving management and adequate sports facilities to support Squash coaching. Looking for a national or international licensed coach is a solution to improve the quality of coaching. Broader socialization about the sport of Squash in the community, including villages, is expected to attract more participants. In addition, finding sponsors and other funding sources will help overcome the problem of lack of funds. In conclusion, coaching Squash in Riau Province has management, facilities, and athlete achievements advantages. Keywords: SWOT and Squash Coaching